Thick as thieves [large type] - Brown, Sandra, 1948- (Grand Central Publishing Large Print, 2020)
"Twenty years ago in the dead of night, four seemingly random individuals pulled the ultimate heist and almost walked away with half a million dollars. But by daybreak, their plan had been shot to hell. One of them was in the hospital. One was in jail. One was dead. And one got away with it. Arden Maxwell, the daughter of the man who disappeared all those years ago, presumably with the money, after murdering his accomplice, has never reconciled with her father's abandonment of her and her sister. After countless personal setbacks she decides to return to her family home near mysterious Caddo Lake, and finally get answers to the many questions that torment her. Little does she know, two of her father's co-conspirators, a war hero and a corrupt district attorney, are watching her every move."--